Protective effect of 3-(naphthalen-2-yl(propoxy)methyl) azetidine hydrochloride on hypoxia-induced toxicity by suppressing microglial activation in BV-2 cells - Kim, Jiae; Kim, Su-Min; Na, Jung-Min; Hahn, Hoh-Gyu; Cho, Sung-Woo; Yang, Seung-Ju (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2016)
We recently reported the anti-inflammatory effects of 3-(naphthalen-2-yl(propoxy) methyl) azetidine hydrochloride (KHG26792) on the ATP-induced activation of the NFAT and MAPK pathways through the P2X7 receptor in microglia. To further investigate the underlying mechanism of KHG26792, we studied its protective effects on hypoxia-induced toxicity in microglia. The administration of KHG26792 significantly reduced the hypoxia-induced expression and activity of caspase-3 in BV-2 microglial cells. KHG26792 also reduced hypoxia-induced inducible nitric oxide synthase protein expression, which correlated with reduced nitric oxide accumulation. In addition, KHG26792 attenuated hypoxia-induced protein nitration, reactive oxygen species production, and NADPH oxidase activity. These effects were accompanied by the suppression of hypoxia-induced protein expression of hypoxia-inducible factor 1-alpha and NADPH oxidase-2. Although the clinical relevance of our findings remains to be determined, these data results suggest that KHG26792 prevents hypoxia-induced toxicity by suppressing microglial activation.